Unraveling the Fabric of Teacher Leadership in the Classroom: A Conceptual Model - Gaughran, Benjamin (2016)
Policy makers and governments are continually concentrating on school improvement. Much of the rhetoric of current school improvement literature focuses on the idea that effective leadership is key to achieving sustained school improvement. This literature is usually tied up in senior and middle management levels of leadership. Little attention is given to the role of teacher leadership in the classroom in school improvement. Furthermore, there is a lack of understanding of what teacher leadership in the classroom actually looks like. Against a backdrop of organisational theory, this study aims to unravel the fabric of teacher leadership in the classroom and provide a conceptual model of specific characteristics needed in effective teacher leaders. Additionally, this study will reveal the voice of teachers and their understanding of teacher leadership in the classroom. The model suggested can be used as a basis to improve the quality of teacher leaders and, therefore, improve pupil progress and impact on whole school improvement.